Halophytes as new model plant species for salt tolerance strategies - Mann, Anita; Lata, Charu; Kumar, Naresh; Kumar, Ashwani; Kumar, Arvind; Sheoran, Parvender (Frontiers in Plant Science, 2023)
Soil salinity is becoming a growing issue nowadays, severely affecting the world's most productive agricultural landscapes. With intersecting and competitive challenges of shrinking agricultural lands and demand of food, there is an emerging need to building resilience for adaptation to anticipated climate change and land degradation. This necessitates the deep decoding of gene pool of crop plant wild relatives which can be accomplished through salt-tolerant species, such as halophytes, in order to reveal the underlying regulatory mechanisms. Halophytes are generally defined as plants able to survive and complete their life cycle in highly saline environments of at least 200-500 mM salt solution. The primary criterion for identifying the salt tolerant grasses (STGs) includes presence of salt glands on leaf surface and Na+ exclusion mechanism since the interaction and replacement of Na+ and K+ greatly decides the survivability of STGs in saline environments. During the last decades or so, various salt tolerant grasses/halophytes have been explored for mining of salt tolerant genes and testing their efficacy in improving limit of salt tolerance in crop plants. Still the utility of halophytes is lacking due to non-availability of any model halophytic plant system as well lack of complete genomic information. Although, till date Arabidopsis (Arabidopsis thaliana) and salt cress (Thellungiella halophila) are being used as model plants in most salt tolerance studies but these plants are short lived and can tolerate salinity for shorter duration only. Thus, identifying the unique genes for salt tolerance pathways in halophytes and their introgression in related cereal genome for better tolerance to salinity is the need of hour. Modern technologies including RNA sequencing, genome wide mapping etc along with advanced bioinformatics programmes have advanced the decoding of whole genetic information of plants and development of probable algorithms to correlate stress tolerance limit and yield potential. Hence, this article has been compiled to explore the naturally occurring halophytes as potential Model plant species for abiotic stress tolerance and further breeding crop plants for enhancing salt tolerance through genomic and molecular tools.